KOORDINASI ANTARA KEPALA SEKOLAH DAN PENGAWAS DALAM PELAKSANAAN SUPERVISI AKADEMIK - Yulis Setyawati; Rohiat Rohiat; Zakaria Zakaria (Manajer Pendididikan, 2017)
The purpose of this study was to discribe how the general objective of the research is to describe the coordination between principal and supervisor in the implementing of instructional supervision is in the Elementary Schools of Karang Tinggi Sub District, Central Bengkulu Regency. The result of the study The result of the research showed that the coordination between principal and supervisor in the implementation of instructional supervision. That can be seen from the absence of coordination between principal and supervisor in the arrangement of instructional supervision planning program, there is no coordination intensity between principal and supervisor in the implementation of academic supervision, the coordination of monitoring and evaluating between principal and supervisor has not run optimally, and there is no coordination of result follow-up between principal and supervisor in the implementation of academic supervision.